Fintechs’ Future in Kenya: Does Social Influence Matter? - Mohammed; Mugambi Ireri, Edward (Journal of African Business, 2021)
ABSTRACT This paper investigates the role of social influence on continuous intention to use Fintech mobile money lending app services in Kenya. A sample of 342 respondents was selected using convenience sampling. Data was analyzed using a structural equation modeling technique with the AMOS version 24 software. The study found out that social influence has a significant direct role on perceived security, satisfaction and continuous intention to use mobile money lending services. The moderating role of social influence strengthens the positive relationship between perceived security and perceived usefulness on one hand and perceived satisfaction and continuous intention to use mobile money lending services, especially among mobile money lending apps users on the other hand. In addition, Kenyans will continue to use mobile money lending app services if they remain useful, secure, satisfactory and meet their expectations.
Hersi Warsame
ORCID Mohammed Hersi Warsame http://orcid.org/0000-0003-0202-1449 Edward Mugambi Ireri http://orcid.org/0000-0001-8356-9187
Keywords: Continuous intention to use; Mobile money lending apps; Perceived satisfaction; Perceived security; Perceived usefulness; Social influence